Contribución al estudio del fósforo en suelos ácidos. 1: Características de adsorción y fracciones de fósforo en una tierra parda del noroeste de España. - Arines, J; Alvarez, M.T. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
P adsorption isotherm and P fractions were used to study the P adsorption characteristics of an acid brown soil from Galicia (North West of Spain). Adsorption data were adjusted to Freundlich, Langmuir, and Gunary equations, and to the parameter X/logC proposed by Bache and Williams. Results show that data adjusted well to the Freundlich equation for equilibrium concentration values between 1-12 ppm P. Between 0-12 ppm P, the adsorption is best described by the Gunary equation, It is suggested the operation of two mechanisms with maximum adsorption values of 226 and 463 ppm P. Fractionation of soil P shows that adsorption occurs mainly as P-AL.